The Mysterious MBI People - Cohen, Rudolph - (The Biblical archaeology review, 1983)
One of the most obscure periods in the history of Palestine is the Middle Bronze I period (commonly referred to as MBI) which extended from about 2200 B.C. to about 2000 B.C. Who were the MBI people? We really don’t know. On the basis of my research, I would suggest that they were a […]